Technology Management: developing a critical perspective. (4th August 2014) - Jones, Oswald; Green, Kenneth; Coombs, Rod
Technology Management is a topic which is currently attracting considerable interest from academics and practitioners. There is particular concern to ensure that technological issues are incorporated into a firm's strategic planning. Consequently, the Technology Management literature concentrates on describing the tools and techniques for analysing the firm's technological portfolio. We agree that the strategic management of technology is key to any attempt to improve the long–term performance of UK manufacturing. However, in this paper we argue that there is a need for those concerned with the study and teaching of Technology Management to adopt a more critical perspective. There is a danger that embracing a technological rationality might obscure the broader social and environmental issues which need to be considered when linking technology to corporate strategy.